The Influence of Service Quality and Information Systems for Rural and Urban Land and Building Tax Collection (PBB P2) on the Effectiveness of P2 PBB Payments at The Congeang Kecamatan District Office - Dina Diandri; Tita Kartika; Gunawan Wibisana (LPPM Universitas Sebelas April, 2022)
The core problem of this research is the effectiveness of the payment of Rural and Urban Land and Building Tax (PBB P2) at the Conggeang DistrictOffice, Sumedang Regency.The purposeof this study was to determine how much influence the quality of service and information systems forcollecting Land and Building Tax (PBBP2) onthe effectiveness of PBB P2 payments at the Conggeang District Office, Sumedang Regency. This study uses quantitative methods. Thenumberof samples in this study were 100 respondents usingmethod random sampling. The analysis used is multiple linear regression analysis. Data processing using the SPSS for windows 25 program. The results of this study indicate that thequality of service and information systemsfor Rural and Urban Land and BuildingTax (PBBP2) has asignificant effectonthe effectiveness of PBB P2 paymentsin Conggeang District, Sumedang Regency. This is indicated by the regression equation Y=12,516+0,154X1+ 0,539X2+ 3,427. The probability value is less than 0.05 and the calculated f value isgreater than f table, the results of the coefficient of determination test to determine the amount of contribution provided by the service and information system for Rural adnd Urban Land and Building Tax (PBBP2) on the effectiveness of (PBBP2) payments of 46.9%. Then according to the t-test the quality of service has a significant effect on the effectiveness of PBB P2 payments seen from t count > t table (1.685>1.660) and the information system for Rural and Urban Land and Building Tax (PBBP2) has asignificant effect on the effectiveness of PBB P2 payments seenfromt count > ttable (7.172 > 1.660).